Relationship between dietary carbohydrate quality index and metabolic syndrome among type 2 diabetes mellitus subjects: a case-control study from Ghana - Sufyan Bakuri Suara; Fereydoun Siassi; Mahama Saaka; Abbas Rahimiforoushani; Gity Sotoudeh (BMC, 2021)
Abstract Background Dietary carbohydrate quality may play an important role in disease development. We evaluated the association between carbohydrate quality index (CQI) and the odds of metabolic syndrome (MetS) in type 2 diabetes mellitus (T2DM) subjects in Ghana. Methods In this case-control study, we analyzed data using 124 T2DM subjects. We obtained dietary information using 2-day 24-h dietary recalls. We calculated CQI from dietary fiber, glycemic index, whole grains/total grains ratio, and solid carbohydrates/total carbohydrates ratio. Serum lipid profiles were measured after an overnight fast of 8-12 h. Results Upon adjustments for the effects of covariates, the CQI showed a positive association with high-density lipoprotein cholesterol concentration (beta coefficient (β) = 0.24; standard error (SE) = 0.20; P for trend = 0.01), and an inverse relationship with waist circumference (β = − 17.29; SE = 4.00; P for trend < 0.001), systolic blood pressure (β = − 15.74; SE = 4.69; P for trend < 0.001), diastolic blood pressure (β = − 7.23; SE = 2.97; P for trend = 0.02), and triglyceride concentrations (β = − 0.43; SE = 0.11; P for trend < 0.001). Overall, the CQI had an inverse relationship with the odds of MetS (Odds ratio tertile 3 vs.1 0.05; 95% Confidence interval: 0.01-0.23; p-trend < 0.001). Also, a positive correlation was found between the CQI and fiber, but the CQI showed a negative relationship with dietary glycemic index. Conclusions The present results suggest an inverse association between the CQI of a diet and the odds of MetS. The CQI approach of dietary recommendation may be a useful strategy for dietary carbohydrate selection for the prevention of MetS.